Fluktuacja dynamiki i dymorfizm płciowy cech somatycznych, typu budowy i otłuszczenia ciała dzieci i młodzieży w wieku od 4 do 18 lat, środowiska miejskiego regionu warmińsko-mazurskiego - Mrozkowiak, Mirosław; Posłuszny, Michał (Journal of Education, Health and Sport, 2015)
Mrozkowiak Mirosław, Posłuszny Michał. Fluktuacja dynamiki i dymorfizm płciowy cech somatycznych, typu budowy i otłuszczenia ciała dzieci i młodzieży w wieku od 4 do 18 lat, środowiska miejskiego regionu warmińsko-mazurskiego = Fluctuation of dynamics and sexual dimorphism of somatic features, body types and adiposity values in children and adolescents at the ages from 4 to 18 living in the urban areas of Warmia and Mazury. Journal of Education, Health and Sport. 2015;5(7):401-428. ISSN 2391-8306. DOI 10.5281/zenodo.20366 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A401-428 https://pbn.nauka.gov.pl/works/587166 http://dx.doi.org/10.5281/zenodo.20366 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 15.07.2015. Fluktuacja dynamiki i dymorfizm płciowy cech somatycznych, typu budowy i otłuszczenia ciała dzieci i młodzieży w wieku od 4 do 18 lat, środowiska miejskiego regionu warmińsko-mazurskiego Fluctuation of dynamics and sexual dimorphism of somatic features, body types and adiposity values in children and adolescents at the ages from 4 to 18 living in the urban areas of Warmia and Mazury Mirosław Mrozkowiak1, Michał Posłuszny2 1Bioergonsport, Nowa Biała, magmar54@interia.pl http://wadypostawy.republika.pl 2Kręg-Clinic, Prywatna klinika rehabilitacyjnio-ortopedyczna, Poznań Słowa kluczowe: wysokość i masa ciała, wskaźnik BMI i IR. Streszczenie Wstęp. Mimo sekularnego zwiększenia wysokości ciała we wszystkich grupach i płciach, dystanse międzyśrodowiskowe nie wykazywały tendencji malejących, jednak wszystkie populacje dążą do pewnej stabilizacji. Powszechnie stosowany wskaźnik wagowo-wzrostowym BMI umożliwił diagnostykę otyłości i nadwagi, a wskaźnik IR określenie typu budowy ciała. Celem badań jest określenie dynamiki zmian i dymorfizmu płciowego cech somatycznych, typu budowy i otłuszczenia ciała dzieci i młodzieży w wieku od 4 do 18 lat środowiska miejskiego regionu warmińsko-mazurskiego Polski. Metoda i materiał. Z badań uzyskano 13625 obserwacji w tym 7199 wśród dziewcząt i 6426 chłopców. Pomiarów dokonano na wadze lekarskiej z dokładnością do0,5 cm i100 g. Wnioski. 1. Średnia wysokość i masa ciała chłopców w wieku od 4 do 18 lat jest większa niż dziewcząt w tym samym wieku, 2. Wśród dziewcząt i chłopców dominuje smukły typ budowy ciała, w wieku 4 lat przeważa średni. W 14 r.ż. wśród dziewcząt nie występuje typ średni, chłopców tęgi, 3. Odsetek dziewcząt i chłopców z niedowagą utrzymuje się na wysokim poziomie do 8 r.ż., później sukcesywnie obniża się na korzyść optymalnego, 4. Zaobserwowane różnice pomiędzy cechami somatycznymi, typem budowy i otłuszczeniem mogą mieć związek z wyraźniejszym skokiem pokwitaniowym, zachodzącym wśród badanych reprezentujących porównywane regiony kraju. Proces ten może świadczyć o zróżnicowaniu dojrzewania w obrębie porównywanych grup. Key words: body mass and body height, BMI and IR. Abstract Introduction. Despite a spectacular growth in body height among all age groups and sexes, the differences between the rural and urban environments do not show any declining tendency, though all populations are gradually achieving certain stability. Commonly used weight-height indicator (BMI) enables one to diagnose obese and overweight individuals, and IR indicator to determine body types. The aim of the present study is to determine the dynamics of changes and sexual dimorphism of somatic features, body types and adiposity values in children and adolescents at the ages from 4 to 18, living in the urban areas of Warmia and Mazury, Poland. Methods and materials. The conducted research provided one with 13625 observations, including 7199 in girls and 6426 in boys. The data were obtained on a medical scale with accuracy to 0,5 cm and 100 g. Conclusions 1. Average body height and body mass in boys at the ages from 4 to 18 is greater than in girls at the same age. Slim body type is the dominant body type in both female and male populations, though at the age of 4 average body type is prevalent. 2. Among the girls at the age of 14 average body type does not occur and among the boys at the age of 14 a heavy body type does not occur. 3. The percentage of underweight individuals is high for both sexes until the age of 8, and then it gradually decreases leaning towards the normative range. 4. Observed differences in somatic features, body types and adiposity values may be connected to a more dynamic puberty sprout in some individuals coming from the compared regions. This process, in turn, may be a sign of different puberty pace among the compared groups.